Installation for low‑deformation welding of stainless steels with dry ice - F. I. Panteleenko; A. M. Mamonov (Литьë и металлургия)
The article provides a brief factors’ analysis affecting the quality of the welded joint of thin‑sheet austenitic steels and methods for reducing deformations and residual stresses. It is noted that the most expedient is the welding method using a heat sink, which consists in the fact that a cooling source moves behind the welding arc. Proposed and described the design and operation of the installation of low‑deformation welding of stainless steels using dry ice as a cooler, which allows very quickly reducing the metal temperature in the welding area, as well as regulating the welding speed and the amount of dry ice supplied to a given area of the welded joint. The procedure for working on the installation and evaluating the quality of the welded joint is proposed.